Cyprus : Financial Sector Assessment Program Update; Technical Note; Factual Update on Basel Core Principles for Effective Banking Supervision; ASDCS. (IMF Staff Country Reports; Country Report ;, 2009)
This technical note presents Cyprus's Financial Sector Assessment Program Update. The authority has worked to enhance the quality of supervision, inter alia in the organizational area, upgrading the number of staff and staff expertise, and planning to intensify onsite supervision. A single supervisor for all banks operating in Cyprus could enhance the effectiveness and efficiency of supervision and could support the creation of a level playing for all banks.